Islamic Strategies and State Measures Through Legislation for Prevention of Covid-19: Pakistani and Indian Perspective (Al-Qamar, 2021)
Islam is the religion of all times and all places. It is an adaptable, assimilative, and accepting religion that gives an unrivalled blueprint for its members to live a life of distinction. It provides guidance to its adherents in all aspects of life, whether in the past, present, or future. Therefore, if he faces some calamity or tragedy, a true believer still looks towards Islam. The recent epidemic of COVID-19 calls for a step forward in the development of coping mechanisms based on Islamic teachings. As a result, the purpose of this essay is to evaluate the guidelines provided by Islam to its adherents in order to avoid and deal with the pandemic. Immunologists and the World Health Organization (WHO) today believe that over 1500 years ago, Prophet Muhammad (SAW) was also advised as protective measures to remain safe from global contagion. Islam also advocated obtaining medical attention, consuming the right foods and beverages, supplications, and obeying Allah's will (Pre-destination). This study points out that it is impossible to assume that a Prophet with no scientific experience already knew, step by step, around 1,500 years ago, what to do during a pandemic that is still relevant in the twenty-first century. It follows that the primary aims of the Shariah include both the protection of faith and the preservation of life. It also states how Pakistani and Indian states have 23% of Muslims follow these Islamic rules and tackle the pandemic through legislation.
Keywords: Covid-19; Islam; Outbreak; Legislation